Synthesis and antibacterial activity evaluation of N (7) position-modified balofloxacins - Hong, Ge; Li, Weitian; Mao, Lina; Wang, Jiawen; Liu, Tianjun (Frontiers in Chemistry, 2022)
A series of small-molecule fluoroquinolones were synthesized, characterized by HRMS and NMR spectroscopy, and screened for their antibacterial activity against MRSA, P. aeruginosa, and E. coli as model G+/G- pathogens. Compounds 2-e, 3-e, and 4-e were more potent than the reference drug balofloxacin against MRSA and P. aeruginosa (MIC values 0.0195 and 0.039 μg/mL for 2-e, 0.039 and 0.078 μg/mL for each of 3-e and 4-e, respectively). Analysis of the time-dependent antibacterial effect of compound 2-e toward MRSA showed that in the early logarithmic growth phase, bactericidal effect occurred, while in the late logarithmic growth phase, bacterial inhibition occurred, because of concentration effects, and possibly development of drug-resistance. Compound 2-e exhibited low toxicity toward normal mammalian cell lines 3T3, L-02, and tumor cell lines A549, H520, BEL-7402, MCF-7. The compound was not hemolytic. Atomic force microscopy (AFM) revealed that compound 2-e could effectively destroy the membrane and wall of MRSA cells, resulting in outflow of the cellular contents. Docking studies indicated the good binding profile of these compounds toward DNA gyrase and topoisomerase IV. ADMET prediction showed that most of the synthesized compounds followed Lipinski’s “rule of five” and had good drug-like properties. Our data suggested that compound 2-e exhibited potent anti-MRSA activity and is worthy of further investigation.